2012
DOI: 10.1111/j.1447-0756.2012.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality rates for extremely low‐birthweight infants: A regional, population‐based study in Japan during 2005–2009

Abstract: Survival of infants (<1000 g) depends on gestational age, centralization and multiple births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The study subjects consisted of the following patients: maternal transport (primary to secondary center), n = 30; born at a secondary center, n = 48; maternal transport (primary to a tertiary center), n = 34; maternal transport (secondary to tertiary center), n = 68; born at a tertiary center, n = 13; and born at a primary center or at home, n = 2. The detailed characteristics of the mothers and infants have been described previously …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study subjects consisted of the following patients: maternal transport (primary to secondary center), n = 30; born at a secondary center, n = 48; maternal transport (primary to a tertiary center), n = 34; maternal transport (secondary to tertiary center), n = 68; born at a tertiary center, n = 13; and born at a primary center or at home, n = 2. The detailed characteristics of the mothers and infants have been described previously …”
Section: Resultsmentioning
confidence: 99%
“…The protocols for obstetric and neonatal management are basically the same at all perinatal centers in Miyazaki. The management methods are described in our previous paper …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous population-based study on extremely low-birth weight infants, we reported that the perinatal mortality depends on gestational age and centralization, in which the mortality rate was 29% at 22 weeks of gestation, 22% at 23 weeks, 34% at 24 weeks, 7% at 25 weeks, and 6% at 26 weeks [2]. Under these circumstances of perinatal care, we investigated whether the presence or absence of skin lesions may affect neonatal mortality and morbidity in extremely premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes are influenced by many perinatal factors. For example, antenatal factors include obstetrician's attitude [1], gestational age [2], sex [3], antenatal corticosteroid therapy [3], multi fetal pregnancy [4], growth restriction and so on [5,6], and neonatal factors include circulatory and respiratory instability [7], intracranial hemorrhage, Periventricular leukomalacia [8], intestinal perforation [9], and so on.…”
Section: Introductionmentioning
confidence: 99%